Malaysia has final say on Jong nama body say experts - Malay, Mail (themalaysianreserve, 2017)
PETALING JAYA — There is no international law requiring Malaysia to release the body of assassinated Kim Jong-nam to North Korean authorities without the consent of a next of kin, say legal experts.